The relationship between spiritual well-being and hopelessness levels of substance users - Soylar, Pinar; Doğan, Ufuk (My University, 2020)
This study was carried out to investigate the effect of the spiritual well-being of the individuals diagnosed with substance use disorder on their level of hopelessness. The sample of this study consisted of 256 patients who were hospitalized with the diagnosis of substance use disorder in an alcohol and druc addcition treatment center (ADATC) between October 1, 2018 and April 1, 2019. Patients who did not accept to participate in the study and repeated hospitalizations were excluded. The study was carried out with remaining 201 patients. Data were collected using Sociodemographic Information Form, the Spiritual Well-being Scale and the Beck Hopelessness Scale. Mann Whitney U, Kruskal Wallis test and Spearman Correlation analyses were used in the evaluation of the data. The mean age of the participants was 28.59±8.54 and all participants were male. The total score of the participants from the Spiritual Well-being Scale was 109.89±15.88, and from the Beck Hopelessness Scale was 7.33±5.30. In the study, a negative relationship was found between spiritual well-being and hopelessness levels of the patients (p<0.01). There was a negative relationship between patients’ spiritual well-being scores and the number of applications to the inpatient treatment center (p<0.01). There was a positive relationship between patients’ Beck hopelessness scores and the number of applications to the inpatient treatment center (p<0.05). There was a weak negative relationship between patients’ Beck hopelessness scores and their age (p<0.05). As the level of spiritual well-being increased, hopelessness level decreased. It is recommended to provide counseling and care services to increase the patient’s spiritual well-being
Keywords: Madde Bağımlılığı; Psikoloji